Case Report: Penile Squamous Cell Carcinoma Associated With Severe Hypercalcemia and High Levels of Parathyroid Hormone-related Peptide Expressed in Metastatic Skin Tissue - Barcia, Ricardo Enrique (2018)
It is known that high levels of parathyroid hormone-related protein (PTHrP) correlate with a bad prognostic in malignancies. Here we present a patient with advanced penile cancer (PC) without antecedents of human papillomavirus infections and bone metastases but with severe hypercalcemia. By quantitative polymerase chain reaction, we observed high levels of PTHrP messenger RNA in metastatic cutaneous tissue. This is the first reported case in Argentina of hypercalcemia induced by PTHrP in human PC. Furthermore, the association of PTHrP and this disease through quantitative polymerase chain reaction allows us to consider this molecular technique as a novel tool for diagnosis in patients with PC.